Gülen's master piece “pearls of wisdom”: an inspiring source for inner peace and physical strength - Shehu, Fatmir Mehdi (2014)

(untitled)
This study attempts to present Gülen's inspiring thoughts on nurturing inner peace and physical strength in the light of his master piece “Pearls of Wisdom”. This master piece discusses the very nature of the sub-lime worldview initiated and promoted by the Qur’an and Sunnah of Muhammad (s.a.w.). Inspired by the teachings of Islam – Quran and Sunnah, Gülen introduces to both, the Muslim and the non-Muslim read-er the very fundamental elements on which a person’s view of the TRUTH as a whole should be established, developed, implemented and sustained. The balance be-tween a person’s inner aspect of life and the outer aspect of life helps him/her to nurture inner peace and physical strength. This phenomenon has been examined by Gülen in the entire content of his “Pearls of Wisdom.” This research in a very humble way will discuss issues as presented by Gülen in the content of his book “Pearls of Wisdom” dealing with: (1) the true perception of the spiritual, personal, familial and social aspects of life; (2) the genuine approach towards Knowledge and Governance, and (3) the avoidance of worldly traps and comforts by referring to ideal people and their achievements. The researcher believes that the findings of this study will inspire and motivate the contemporary people in general and the Muslims in particular to enhance their relationships with each other. Also, the findings of this study will add to the existing literature on the human peace and coexistence, the contribution of Fethullah Gülen, a contemporary Muslim thinker and scholar.